Coconut varieties for more return - Niral, V; Jerard, B Augustine; Chowdappa, P (Indian Horticulture, 2018)
The research efforts have recorded impressive achievements in terms ofdeveloping new cultivars and production technologies, which whendemonstrated in the field resulted in two-three fold increase in yield. On anational level, research efforts under the aegis of the ICAR, CPCRI, AICRPand SAUs have resulted in the development of 49 improved varieties,including 20 hybrid varieties, capable of producing 2.79-6.28 tonnes ofcopra/ha/year in different parts of the country for cultivation in differentagroclimatic regions within the country, including varieties tolerant to bioticand abiotic stress and specific end uses.